Bridging Systems and Practice: Insights from Nepal’s Frontlines of Health, Education, and Finance - Tripathi, Yashodham (A Bi-annual South Asian Journal of Research & Innovation, 2025)
This twice-a-year South Asian edition of JORI pulls together studies that get right into practice. You know the kind. Stuff happening at hospital bedsides and in classrooms. Or in bank boardrooms and public offices. And even in homes where folks make daily choices as the economy shifts around them. Most of the work here is grounded in Nepal. Still, their points reach across South Asia's common hurdles. Things like lining up policy goals with what actually happens in the field. Or building stronger institutions. And turning solid evidence into outcomes that feel fair for everyone.